ANALISIS STRATEGI SEGMENTATION, TARGETING, POSITIONING PADA PT HASANAH BUBUK SENTOSA - Ariani, Rahma (Politeknik Negeri Medan, 2023)
This study was conducted to determine the effect of Cash Turnover and Receivables Turnover on Return On Assets (ROA) in Food And Beverage Companies Listed on the Indonesia Stock Exchange for the 2015-2017 Period. In this study, researchers used data on the financial statements of companies listed on the Indonesia Stock Exchange which were then analysed using SPSS 22.0. The test results show that cash turnover and accounts receivable turnover have a significant positive effect on Return On Assets (ROA) and there is a simultaneous influence between cash turnover and accounts receivable turnover on Return On Assets (ROA) with an R Square value of 0.461. This shows that the percentage of the effect of cash turnover and accounts receivable turnover on Return On Assets (ROA) simultaneously is 46.1%. While the remaining 53.9% is influenced by other variables outside of the variables of this study.